BALANCING MOTHERHOOD AND ACADEMIC PURSUITS: CHALLENGES AND OPPORTUNITIES FOR NIGERIAN WOMEN - Rosemary Onchi Daniel; Doris Lami Madugu (International Studies Journal)
This study explores the multifaceted challenges and opportunities faced by Nigerian women as they balance motherhood and academic pursuits. Drawing on global and local perspectives, the research highlights the significant barriers these women encounter, including traditional gender roles, institutional gaps, economic pressures, and psychosocial stress. Traditional gender roles in many Nigerian communities place primary responsibility for childcare and household duties on women, significantly limiting their time and energy for academic endeavors. The primary objective is to identify and analyze these challenges while exploring potential strategies for support and empowerment. Guided by the theoretical framework of liberal feminist theory, which emphasizes gender equality and women's rights. A sample size of 374 Nigerian mothers on academic journey from various universities was selected using a mixed-methods approach. Quantitative data were collected through questionnaires, while qualitative data were obtained via in-depth interviews. Findings reveal that traditional gender roles significantly limit the time and energy women can dedicate to academic pursuits. Institutional barriers, such as inadequate childcare facilities and inflexible working hours, further exacerbate these challenges. Economic pressures and the high cost of childcare add to the financial burden, while psychosocial stress of juggling multiple roles negatively impacts mental health and academic performance. The study emphasized the urgent need for policy reforms and supportive measures within academic institutions. Recommendations include the implementation of family-friendly policies, establishment of support networks, and promotion of women's empowerment programs. These steps are essential for a more equitable academic environment, enabling Nigerian women to successfully balance motherhood and academic careers.